2011
DOI: 10.1186/1471-2407-11-314
|View full text |Cite
|
Sign up to set email alerts
|

Versican but not decorin accumulation is related to malignancy in mammographically detected high density and malignant-appearing microcalcifications in non-palpable breast carcinomas

Abstract: BackgroundMammographic density (MD) and malignant-appearing microcalcifications (MAMCs) represent the earliest mammographic findings of non-palpable breast carcinomas. Matrix proteoglycans versican and decorin are frequently over-expressed in various malignancies and are differently involved in the progression of cancer. In the present study, we have evaluated the expression of versican and decorin in non-palpable breast carcinomas and their association with high risk mammographic findings and tumor characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 56 publications
(85 reference statements)
1
34
0
2
Order By: Relevance
“…DSPGs expression was described to be increased in breast cancer fibroadenoma compared to healthy tissue [11]. A common finding is that matrix secreted CS/DSPGs such as decorin and versican are deposited in tumor stroma [12, 13] and are related to aggressive phenotype in breast cancer [14–16]. Relapse in women with node-negative breast cancer is related to the level of versican deposited in peritumoral stroma [14, 17].…”
Section: Extracellular Matrices In Breast Cancer: Focus On the Promentioning
confidence: 99%
See 1 more Smart Citation
“…DSPGs expression was described to be increased in breast cancer fibroadenoma compared to healthy tissue [11]. A common finding is that matrix secreted CS/DSPGs such as decorin and versican are deposited in tumor stroma [12, 13] and are related to aggressive phenotype in breast cancer [14–16]. Relapse in women with node-negative breast cancer is related to the level of versican deposited in peritumoral stroma [14, 17].…”
Section: Extracellular Matrices In Breast Cancer: Focus On the Promentioning
confidence: 99%
“…It is accumulated in the preclinical phase of breast cancer in non-palpable breast carcinomas and is associated with risk factors such as increased mammographic density and malignant appearing microcalcifications [16]. Versican is increased in fibroadenoma [11] and the elevated levels of stromal versican are associated with increased risk and rate of relapse in women with node-negative breast cancer [14, 17].…”
Section: Versican: a Tumor Stroma-associated Proteoglycan In Breasmentioning
confidence: 99%
“…Of note, immunohistochemical examination showed that syndecan-1, which was redistributed from the epithelium to the stroma, was over 10-fold higher in aggressive breast tissue compared to normal tissue [134]. Similarly, fibroblast-secreted versican, promotes tumor growth, migration, and metastasis in breast, ovarian, and prostate cancer [135139], and is a product of paracrine TGF-β1 signaling in the latter. Stromal versican is associated with relapse and poorer outcome in cancer patients [140–142].…”
Section: Proteoglycansmentioning
confidence: 99%
“…According to our previous data [25,27], we can assume that this targeting occurs in part through interaction between N6L and cellsurface nucleolin, which is overexpressed by tumor cells. However, several studies have shown that sulfated GAGs are overexpressed by tumor cells [31,32]. Analysis of the quantification of GAG have been evaluated from extract of tissue using carbazole assay and CS disacharide content.…”
Section: Discussionmentioning
confidence: 99%